Pengaruh Kualitas Produk, Word of Mouth, dan Store Image terhadap Keputusan Pembelian: Studi pada Pengunjung Toko Amigo Pedan - Wita Marantika; Sarsono Sarsono (Universitas Proklamasi 45 Yogyakarta, 2020)
Marketing is the process of selling goods and services that aims to meet and satisfy customer wants. The purpose of this study is to determine the effects of product quality, word of mouth, and store image on purchasing decisions in Amigo Pedan store, Klaten, Central Java, Indonesia. The population in this study is the visitors of Amigo Pedan with a sample of 91 respondents. The sampling technique used in this study was incidental sampling. Primary data was collected using questionnaires. This study used multiple linear regression analysis. The results of this research showed that product quality, word of mouth, and store image have significant and positive effects on purchasing decisions in the store, simultaneously. But, only the word of mouth has a significant effect on customers’ purchasing decisions in the store, partially.